Predictive Factors of Neutropenia Following First Cycle of Chemotherapy in Patients with Non-Hodgkin’s Lymphoma in Bali, Indonesia - Pratiwi, Made Sindy Astri; Agustini, Made Priska Arya; Yani, Made Violin Weda; Rena, Ni Made Renny Anggreni (International Journal of Integrated Health Sciences, 2025)
Background: Chemotherapy-induced neutropenia (CIN) is a common hematologic toxicity that increases infection risk, hospitalization, and treatment delay. Limited data exist on predictive factors of CIN among non-Hodgkin’s lymphoma (NHL) patients in Indonesia, particularly in Bali.Objective: To identify predictive factors of neutropenia following the first cycle of chemotherapy in patients with NHL at Prof. I.G.N.G Ngoerah General Hospital, Bali, Indonesia.Methods: This retrospective cohort study included all NHL patients treated from 2020–2023. Eligible patients were aged ≥18 years, received CHOP-based regimens with or without rituximab, and did not receive G-CSF prophylaxis. Data were obtained from medical records. Assessed risk factors were age, gender, BMI, comorbidities, histopathology grading, extranodal involvement, ECOG status, Ann Arbor stage, IPI score, chemotherapy regimen, pre-treatment blood count, eGFR, LDH, and albumin. The incidence of neutropenia was evaluated after the first chemotherapy cycle.Results: The mean age of the eligible patients (n=112) was 54.53 ± 14.64 years; 46 of them (41%) developed neutropenia. Significant factors associated with neutropenia were histopathology grading (p = 0.030), Ann Arbor stage (p = 0.048), IPI score (p = 0.037), chemotherapy regimen (p = 0.019), and LDH above normal (p = 0.049). Multivariate analysis identified high IPI scores (p = 0.016; OR 6.375; 95% CI 1.416–28.698) and CHOP regimen (p = 0.016; OR 3.033; 95% CI 1.230–7.476) as independent predictors of CIN.Conclusion: High IPI scores and CHOP regimens are strong predictors of neutropenia after the first chemotherapy cycle in NHL patients. Early identification of high-risk patients is essential for preventive management and improved treatment outcomes.